BUILD THE SOUL ENTREPRENEUR FROM AN EARLY AGE AS A MEANS OF CREATING A GENERATION KHOIRU UMMAH WITH THE EXISTENCE OF A SUPERIOR HUMAN RESOURCES - Anas Rangga (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2020)
In the face of the current era and the next era, challenges that currently applies is the readiness of human resources in relation to how the progress of this land to the future. Khairu ummah in the language means the best people, in the current context of the generation that capable to manage themselves and able to resolve the matter of life to support life akherat. Conceptually,